ANALISIS INOVASI DAN KREATIVITAS TERHADAP KINERJA KARYAWAN INDUSTRI SANDAL DAN SEPATU DI DESA WEDORO DI ERA PANDEMI COVID-19 - Rivaldi Adi Yahya; Gendut Sukarno (SOSIOEDUKASI, 2021)
Small and Medium Enterprises (SMEs) are an important part of the economy of a country or region. Various SME development efforts have been carried out, one of which is by generating and creating jobs by starting new businesses in the SME sector. Production in the sandal and shoe industry in Wedoro village, Sidoarjo decreased in 2020 by 4000 Kodi due to the Covid-19 pandemic. This is the concern of the owner of the industry to better understand the desires of consumers who want new innovations for the products sold so that in the following year they can increase. This study aims to analyze the effect of innovation and creativity on the performance of sandal and shoe industry employees in Wedoro Village in the Covid-19 pandemic era. The sampling technique in this research is census sampling. The population in this study is the Owner of the Sandal and Shoe Industry in Wedoro village, with total of 30 people. The data were analyzed using the Partial Least Square (PLS) approach. The results showed that Innovation and Creativity simultaneously had a positive effect on Employee Performance in the Sandal and Shoe Industry in Wedoro Village during the Covid-19 pandemic era.